COMPARISON OF ANTI ASTHMA ACTIVITY BETWEEN EXTRACT AND OIL Nigella sativa ON HISTOPATHOLOGY OF BRONCHIAL EPITHELIAL IN ASTHMA MICE - Dian Arsanti Palupi; Salwa Rahmawati; Annis Rahmawaty; Endra Pujiastuti (Universitas Muhammadiyah Magelang, 2020)
Asthma is an inflammatory disease or chronic airway inflammation. Nigella sativa extract and oil are proven to be used to improve airway inflammation. This study consisted of 7 groups. The normal group (K1), negative group (K2), theophylline (K1), Nigella sativa extract (K4), Nigella sativa oil (K5). 0.9% intraperitoneally, and on the 14th day, the mice were re-sensitized intraperitoneally with a 20µg OVA + 2 mg of Alhydrogel in 1 mL of sterile NaCl 0.9%. On the 21st, 23rd, 25th day, the OVA1% was inhaled. On the 26th to 39th day, the K3 mice were given theophylline 0.338 mg/day, K4 mice were given Nigella sativa extract at a dose of 1 mL/day and K5 mice were given Nigella sativa oil at a dose of 0.1mL / day. On the 40th day, the mice were terminated for analysis of the thickness of the bronchial epithelium. Comparison between groups of Nigella sativa extract on average 15.5 ± 2.22 µm and Nigella sativa oil average of 14.05 ± 3.87 µm p-value = 0.488 means that between the Nigella sativa extract group and Nigella sativa oil there was no difference meaningful. statistically as an antiasthma in decreasing the size of the thickness of the bronchial epithelium